No-fault compensation for medical injuries: trends and challenges - Jahn Kassim, Puteri Nemie (World Association of Medical Law, 2014)
As an alternative to the tort or fault-based system, a nofault compensation system has been viewed as having the potential to overcome problems inherent in the tort system by providing fair, speedy and adequate compensation for medically injured victims. Proponents of the suggested no-fault compensation system have argued that this system is more efficient in terms of time and money, as well as in making the circumstances in which compensation is paid, much clearer. However, the arguments against no-fault compensation systems are mainly on issues of funding difficulties, accountability and deterrence, particularly, once fault is taken out of the equation. Nonetheless, the no-fault compensation system has been successfully implemented in various countries but, at the same time, rejected in some others, as not being implementable. In the present trend, the no-fault system seems to fit the needs of society by offering greater access to justice for medically injured victims and providing a clearer “road map” towards obtaining suitable redress. This paper aims at providing the readers with an overview of the characteristics of the no fault compensation system and some examples of countries that have implemented it.